Teachers’ digital discourse: knowledge exchange and implicated impoliteness - Dias, Isabela Soares de Almeida; Marçal , Fernanda Rodrigues (The ESPecialist, 2025)
This study examines English teachers’ digital discourse in online knowledge exchange platforms, focusing on aspects of epistemic authority and implicated impoliteness. Through analysis of texts in two blogs offering proficiency exam preparation tips, the study investigates how teachers’ linguistic choices may inadvertently convey impoliteness while attempting to engage readers. The research identifies four key expressions of potential impoliteness: conversational discourse markers, typographic emphasis, authoritative stance indicators, and humorous remarks. These strategies, while aimed at creating an engaging and relatable tone, can sometimes be perceived as patronizing or aggressive. The investigation argues that teachers’ presumed epistemic authority may lead to deviations from conversational maxims, resulting in implicated impoliteness. This research contributes to understanding how digital discourse in educational contexts can both facilitate and hinder effective knowledge exchange, highlighting the need for careful consideration of language use in online teaching environments. Keywords: Knowledge Exchange; Implicated Impoliteness; Teachers’ Digital Discourse.